Turkey and the Possibility of Its Integration into the European Union - Stejskal, Jakub, 1988- (2011)
The thesis will examine the position of Turkey from the point of view of possible entry into the European Union. The opening part will deal with conditions of its entry, Turkey's relations with other member countries will be outlined as well as the issue of its economic development in the last years. The second part will deal with economic insight, where the country will be examined on the basis of economic data, especially in connection with the new members of the European Union.